Production of Protein Fortified Rice Noodles from Glandless Cottonseed Flour - Plernchai Tangkanakul; Somchit Onhem; Mantana Ruamrux; Duangchan Hengsawadi (Agriculture and Natural Resources, 1994)
In order to improve nutritional quality of small strip rice noodles, the low fat glandless cottonseed flour (GCSF) was added at ratio 0, 5, 10, 15 and 20% by weight of broken rice. The overall sensory evaluation of 10-20% GCSF-rice noodles were significant difference from plain rice noodles (0% GCSF-rice noodles) (P<0.05). The acceptability scores were range from 2.9-1.7 (like moderately-likeslightly) compared to plain rice noodles which show score equal to 4.2 (like very much). The texture of the small strip rice noodle addes GCSF was determined by using the instron texture instrument. The results showed that the 20% GCSF ricr noodle was required the lowest maximum resistance force, because it was easy to broken down. The higher protein and fat contents of the 5-20% GCFS-rice noodles were range from 8.9-13.7% and 2.0-3.8%, respectively, while compared to protein and fat contents in plain rice noodles of 6.8% and 1.2%, respectively.